(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper highlights upon the changing approach of visualisation and concepts adopted for persuasion and appeal in advertising. It also explores and scrutinizes the various components of modern advertising such as multimedia, internet, online advertising, digital advertising, mobile advertising, and social networking. The study also attempted to evaluate the advertising campaigns of few assorted brands to understand the application and relevance of cartoons and caricatures in modern Indian advertising, its creative approaches, different visual elements and effective use of various modern age advertising tools and innovations in recent advertisements. Advertising is about striking the right note of the many marketing chords that informs and persuades the consumers to buy a product, service or an idea. Advertising in India is also thriving with the traditional advertising trend with the latest innovative advertising strategies. In a small span of time, Indian advertising has occupied a niche for itself to place it on the global map of advertising which started with the need to sell by town criers and hawkers, was the oldest mode to advertise. As marketers looks for ways to keep pace with technology and media, advertising trend have changed dramatically. Newer technology has shifted the focus from mass promotions to target audiences. The Indian advertising industry is witnessing a sea change from the very time of its inception into the Indian society and culture. The age old advertising trends in India had made a parallel practice with print advertising and other innovative trends like television commercials, outdoor, radio, internet, online advertising etc. The mode of advertising had shifted its focus from traditional media with the advent of new medics of digital advertising. The new media has altered the trend of one way flow of information to interactive sessions, where the consumers have also become a part of the process. So instead of being force fed advertisement, users are now getting empowered to choose from a diversified set of new brands.